Impact of COVID-19 on Oncology Healthcare Providers: The Resilience of a Profession. Issue 2 (31st March 2022) - Marshall, Victoria K.; Mason, Tina M.; Chavez, Melody; Martinez-Tyson, Dinorah; Bugajski, Andrew
Abstract : Background: The novel coronavirus (COVID-19) has plagued countries worldwide. This pandemic has greatly affected healthcare delivery and those providing care to vulnerable, immunocompromised patients undergoing cancer treatment, who are at a higher risk for poorer outcomes related to COVID-19. Objective: The aim of this study was to explore the impact of COVID-19 on oncology healthcare professionals (OHCPs). Methods: An exploratory study design was employed using semistructured interviews. A thematic analysis was completed using Atlas.ti software. Results: Of 30 OHCP participants, most were female (90%), registered nurses (70%), and bachelor's prepared (66%). The following themes emerged: (1) pandemic-related restrictions and stress on personal lives impacted the ability of OHCPs to rejuvenate and reenergize for work; (2) fear of exposure and transmission and concern for high-risk status for contracting COVID-19; (3) limited resources and inconsistent communication about organizational policies caused additional stress, affecting OHCP trust and confidence in the system; (4) concern for the mental health of fellow OCHPs; (5) adaptation and resilience were required amidst shifting workloads, workflow, and new restrictions; and (6) importance of self-care to reduce personal/professional stressors. Conclusions: Oncology healthcare professionals continue to face challenges of COVID-19 on their personal and professional lives yet have shown resilience during these unprecedented times. Implications for Practice: Oncology healthcare professionals need to advocate for appropriate personal protective equipment and reliable mental health support services through employers. They should be engaged in COVID-19 task forces to ensure their challenges are heard and needs are addressed to provide quality oncology care.